Days without end : a novel - Barry, Sebastian, 1955- (Viking, 2016)
Entering the U.S. army after fleeing the Great Famine in Ireland, seventeen-year-old Thomas McNulty and his brother-in-arms, John Cole, experience the harrowing realities of the Indian wars and the American Civil War between the Wyoming plains and Tennessee.